Ca2+ movement and apoptosis induced by deltamethrin in Madin–Darby canine kidney canine renal tubular cells. Issue 1 (2nd December 2014) - Liu, Fang‐Jin; Chou, Chiang‐Ting; Cheng, Jin Shiung; Chang, Hong‐Tai; Liang, Wei‐Zhe; Kuo, Chun‐Chi; Kuo, Soong‐Yu; Kuo, Daih‐Huang; Shieh, Pochuen; Chang, Fang‐Rong; Jan, Chung‐Ren
Abstract: This study explored the effect of deltamethrin, a pesticide, on free Ca 2+ concentration [Ca 2+ ]i, viability, and apoptosis in Madin–Darby canine kidney (MDCK) canine renal tubular cells. Deltamethrin at concentrations between 10μM and 40μM evoked [Ca 2+ ]i rises in a concentration‐dependent manner. The Ca 2+ entry was inhibited by nifedipine, econazole, phorbol 12‐myristate 13‐acetate, and SKF96365. Treatment with the endoplasmic reticulum Ca 2+ pump inhibitor 2, 5‐di‐tert‐butylhydroquinone (BHQ) in a Ca 2+ ‐free medium abolished deltamethrin‐induced [Ca 2+ ]i rise. Treatment with deltamethrin also abolished BHQ‐induced [Ca 2+ ]i rise. Inhibition of phospholipase C (PLC) activity with U73122 abolished deltamethrin‐evoked [Ca 2+ ]i rise. Deltamethrin killed cells at 30–60μM in a concentration‐dependent manner. The cytotoxic effect of deltamethrin was not reversed by prechelating cytosolic Ca 2+ with the acetoxymethyl ester of 1, 2‐bis(2‐aminophenoxy)ethane‐ N, N, N ′, N ′‐tetraacetic acid. Annexin V/propidium iodide staining data suggest that 30–50μM deltamethrin induced apoptosis. Together, in MDCK renal tubular cells, deltamethrin induced [Ca 2+ ]i rises that involved Ca 2+ entry through protein kinase C‐mediated store‐operated Ca 2+ channels, and PLC‐dependent Ca 2+ release from the endoplasmic reticulum. Deltamethrin also induced Ca 2+ ‐independent cell death that might involve apoptosis.